Tourism in Southeast Asia a new direction - Chon, K. S. (Kaye) (New York Haworth Hospitality Press, 2000)
"Here is the essential guide to the exploding tourism and hospitality industries in Southeast Asia and Indochina.You will discover unique cultural aspects of various countries in the region and the impact they can have on tourism and hospitality, as well as industry overviews and current and anticipated trends." "Some of the topics explored in Tourism in Southeast Asia: A New Direction are : cross-border cooperation between Southeast Asian countries; ecotourism opportunities for local communities; existing tourism organizations; the vulnerability of current tourism policies and suggestions for change; the impact of tourism on local communities; and the flow of tourism between Australia and Southeast Asia."--Jacket
Ecotourism in southeast asia Ross K. Dowling -- ourism planning in southeast asia Dallen J. Timothy -- Ecotourism and sustainable tourism development in southeast asia John Edmonds and George Leposky -- Dreams and realities Alan Nankervis -- Impacts of tourism on a local community Taksina Nimmonratana -- Analysis of tourism flows between australia and ASEAN countries Bruce R. Prideaux and Stephen F. Witt -- Coastal tourism in southeast asia Poh Poh Wong -- Preconditions for successful collaborative tourism marketing Jutamas Jantarat and Lesley Williams -- Growth and development of the cruise line industry in southeast asia Amrik Singh -- Vietnam's tourism industry Connie Mok and Terry Lam
Includes bibliographical references (pages 115-118) and index.
Keywords: Tourism -- Asia, Southeastern